The Use of Raft Strategy (Role, Audience, Format, Topic) Assisted by Wordwall Media on Grade VII Students in Learning to Writing Descriptive Texts - Muhamad Ersa Kaisar; Dheni Harmaen; Yeni Cania Puspita (Journal of Practice Learning and Educational Development, 2025)
This study discusses the low ability of students in writing descriptive texts. One of the factors that influences the low ability to write descriptive texts is the use of learning strategies and learning media that are less innovative and monotonous so that students feel bored when learning to write descriptive texts. The purpose of this study was to test the effectiveness of the RAFT (Role, Audience, Format, Topic) strategy assisted by Wordwall media in learning to write descriptive texts, in this study, namely quantitative experiments, with a Quasi Experimental design. The RAFT strategy assisted by Wordwall media is effective in learning to write descriptive texts. This can be proven from the results of the N-Gain test which shows the average value obtained by the experimental class, namely 77.2725> 76 so that it can be said that RAFT assisted by Wordwall media is categorized as effective. It can also be seen from the results of the average pretest and posttest scores of the two classes. The average pretest score of the experimental class was 56.2 and the average posttest score of the experimental class was 86. While the average pretest score of the control class was 47.2 and the average posttest score of the control class was 60.8. In the experimental class there was an increase in the average score of 29.8. While in the control class there was an increase in the average score of 13.6. With this, the learning was carried out successfully.